ADAPTED FOOTGOLF: THE PROCESS OF ADAPTING A SPORT FOR PEOPLE WITH DISABILITIES - Reis, Rafael Estevam; Stdrezk, Vinicius Bernardo; Moreira, Paulo Roberto (UNESP, 2020)
The main objective of this study is to present the adaptation of the footgolf modality for people with disabilities. The work was divided into two moments, initially it was necessary to focus on conceptually presenting Footgolf and the Adapted Sport movement. In a second step, we focus our efforts on presenting the classes created for the process of adapting the Footgolf modality, explaining the process step by step and detailing the characteristics of each of these groups and their deficiencies. For this purpose, a demonstrative table was created, later unraveled. We chose to create five functional classes, covering all existing disabilities (physical, visual, intellectual and hearing impairment) where each class refers to a group of disabilities and their specificities. The process of adapting a modality for people with disabilities is complex and time-consuming, in the sense of standardizing its rules in several countries and continents. When creating this modality, we do not intend to define the rules and classes definitively, this is the moment to organize sporting events where Adapted Footgolf is played, played, analyzed, and improved, so that it continues to develop and seek the necessary alignment so that the practice of sports is more and more adequate. Finally, we hope that more and more people with disabilities will enjoy this sport, and that conventional and adapted Footgolf can grow and develop in parallel. Received on: 04/27/2020 Reformulated on: 06/17/2020 Accepted: 06/21/2020